Bounded thinking intellectual virtues for limited agents - Morton, Adam. (Oxford : Oxford University Press, 2013)
Adam Morton offers a new account of the virtues of limitation management: intellectual virtues of adapting to the fact that we cannot solve many of the problems that we can describe. He argues that the best response to many problems depends not on the most rationally promising solution, but on the most likely route to success.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Nov. 13, 2012).
Keywords: Virtue; Intellect; Practical reason